Building exterior wall coating and preparation method thereof
Through the combination of composite inorganic-organic hybrid film-forming base materials and nano-composite flame-retardant fillers, the comprehensive performance problems of exterior wall coatings in high-rise buildings and extreme climate areas have been solved, and a coating with high flame retardancy, long-term weather resistance and self-cleaning ability has been achieved, thereby improving the mechanical strength and construction efficiency of the coating.
Patent Information
- Application Number
- CN202511272593.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-08
- Publication Date
- 2025-10-17
- Estimated Expiration
- 2045-09-08
AI Technical Summary
Existing exterior wall coatings are difficult to achieve the comprehensive performance of high flame retardancy, long-term weather resistance, intelligent self-cleaning and environmental friendliness in high-rise buildings and extreme climate zones. They also have problems such as high brittleness, poor adhesion, easy cracking, poor high temperature resistance, insufficient flame retardancy, easy yellowing, uneven dispersion, and easy pollution.
A multi-level flame-retardant and self-cleaning coating is formed by combining a composite inorganic-organic hybrid film-forming base material, a nano-composite flame-retardant filler, a bio-based thickener, a light-responsive hydrophobic additive and a low-foaming wetting dispersant through electrostatic self-assembly, interpenetrating network and gradient curing technology.
It achieves high flame retardancy, long-term weather resistance, self-cleaning ability and environmentally friendly coating performance, improves the mechanical strength, adhesion and construction efficiency of the coating, and reduces production energy consumption and maintenance costs.
Smart Images

Figure CN120795720A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of building coatings, in particular to a building exterior wall coating and a preparation method thereof. BACKGROUND
[0002] As an important part of building protection system, the performance of exterior wall coating is directly related to the durability, safety and aesthetics of the building. Traditional exterior wall coating is mainly composed of organic resin or inorganic silicate material as film-forming binder, supplemented by pigments, fillers and functional additives. According to the functional requirements, the products on the market are mainly divided into decorative type, waterproof type, heat insulation type and flame retardant type, etc. With the improvement of building safety standards and the strictness of environmental protection regulations, modern exterior wall coating needs to have high flame retardancy, weather resistance, self-cleaning ability and environmental friendly characteristics, which puts higher requirements on the formulation design and preparation process of the material. However, there are still the following bottleneck problems to be solved in the prior art:
[0003] Traditional inorganic coating has high hardness and weather resistance, but it is brittle, has poor adhesion, and is easy to crack due to deformation of the substrate; while organic coating has excellent flexibility, but it has poor high temperature resistance, insufficient flame retardant performance, and is prone to yellowing and aging under long-term exposure to ultraviolet light. The single binder system is difficult to achieve the synergistic optimization of hardness and flexibility, and cannot meet the long-term protection requirements under complex climate conditions. The existing flame retardant coating mostly uses a single flame retardant, which has the problems of high addition amount and uneven dispersion. The coating thickening agent generally relies on synthetic polymer materials, which has the problems of poor biodegradability and high VOC emission. Although natural polymer materials are environmentally friendly, they have poor shear stability and are prone to water separation and sedimentation during storage, which cannot meet the rheological performance requirements of high solid content coating. Traditional super-hydrophobic coating mostly uses fluorine-containing resin or silicone material, which has a high static contact angle, but lacks dynamic self-cleaning ability. Pollutants are easily adhered to the surface of the coating, and long-term ultraviolet radiation will cause degradation of the fluorine-containing segment, resulting in a significant decrease in hydrophobicity. In addition, the compatibility of the existing hydrophobic additives and flame retardant fillers is poor, which easily causes defects in the microstructure of the coating. The dispersion stability of nano fillers in high solid content coating is poor, and traditional mechanical stirring easily introduces air bubbles, resulting in defects such as pinholes and orange peel in the coating film. In addition, a single spraying process cannot achieve the gradient distribution of functional components, and inorganic-organic phase separation phenomenon is common during the curing process, which affects the density and interfacial bonding strength of the coating.
[0004] The above problems restrict the application of exterior wall coating in high-rise buildings, extreme climate regions and scenes with strict fire safety requirements. Therefore, it is of great importance to develop an exterior wall coating with high flame retardancy, long-term weather resistance, intelligent self-cleaning and environmental friendly characteristics. SUMMARY
[0005] In order to solve the problems in the background art, the present application provides a building exterior wall coating, which is prepared from the following raw materials by weight:
[0006] Composite inorganic-organic hybrid film-forming base: 50 parts, prepared by mixing potassium sodium silicate solution and modified polyacrylate emulsion containing 3% phosphate functional monomer at a mass ratio of 1:1.2;
[0007] Nanocomposite flame retardant filler: 28 parts, including Mg-Al layered double hydroxy composite metal oxide LDH and nano cerium oxide in a mass ratio of 3:1 A composite, wherein the LDH loading mass fraction is 5% of zinc borate;
[0008] Bio-based thickener: 2 parts, prepared by mixing hydroxypropyl guar gum and sodium alginate in a mass ratio of 2:1;
[0009] Photoresponsive hydrophobic additive: 0.8 parts, which is fluorinated silicone-modified titanium dioxide nanoparticles;
[0010] Low foam wetting and dispersing agent: 0.7 parts, polyether modified polysiloxane;
[0011] Deionized water: balance.
[0012] Furthermore, the chemical formula of the Mg-Al layered bishydroxy composite metal oxide is , its preparation process is as follows:
[0013] First, and Prepare mixed salt solution in a molar ratio of 3:1, and mix with The precipitant was co-precipitated for 2 hours and the precursor was obtained by centrifugation and washing. ; Then hydrothermally treated at 120-140℃ for 12 hours, spray dried to obtain a high crystallinity intermediate; finally dispersed in The solution was ion exchanged at 50℃ for 24 hours. Completely replace interlayer After washing and drying, the target product was obtained .
[0014] Furthermore, the preparation method of the bio-based thickener is as follows: natural guar gum is used as a raw material, and is reacted with propylene oxide in a molar ratio of 1:1.2 at 60°C under alkaline conditions for 4 hours, and a hydroxyl group is introduced through a hydroxypropyl substitution reaction. Hydroxypropyl guar gum is obtained after ethanol precipitation and drying; brown algae is used as a raw material, and high-purity sodium alginate is obtained after decalcification with dilute hydrochloric acid, alkaline extraction with sodium carbonate, filtration, and ethanol precipitation; hydroxypropyl guar gum and sodium alginate are dissolved in deionized water in a mass ratio of 2:1, and stirred at 50°C for 1 hour to form a hydrogen bond-ionic bond synergistic network, and finally a bio-based thickener is obtained.
[0015] Further, the preparation method of the light-responsive hydrophobic adjuvant is as follows: tetrabutyl titanate is mixed with anhydrous ethanol, diluted nitric acid is added dropwise for hydrolysis, aging at 60℃ for 12h, centrifugation to obtain titanium dioxide with a particle size of 20-50nm ; the is dispersed in isopropyl alcohol, perfluorooctyl triethoxysilane is added, reflux reaction is carried out at 80℃ for 6h, and the fluorine-containing segment is grafted on the surface through siloxane hydrolysis and condensation ; the light response characteristic is strengthened: ultraviolet light irradiation treatment is carried out for 2h, and the specific surface area of the final product is ≥150 .
[0016] Further, the preparation method of the low-foaming wet dispersant is as follows:
[0017] Octamethylcyclotetrasiloxane D4 is used as a monomer, hexamethyldisiloxane is used as an end-capping agent, ring-opening polymerization is carried out at 90℃ for 6h under the catalysis of 1% mass fraction of sulfuric acid, polydimethylsiloxane PDMS with a viscosity of 500-800mPa·s is obtained, PDMS and allyl polyoxyethylene ether are mixed in a molar ratio of 1:1.2 under the action of a platinum catalyst, a polyether-siloxane block structure is formed through a hydrosilylation reaction at 110℃ for 5h, the dynamic surface tension is reduced to ≤30mN / m through the steric hindrance effect of the polyether segment, and the final product has a foaming height of <10mm.
[0018] The application provides a preparation method of a building exterior wall coating, and comprises the following steps:
[0019] S1. A potassium sodium silicate solution and a modified polyacrylate emulsion are premixed at 50℃ under stirring at 300rpm for 1h to form a composite base;
[0020] S2. LDH and nano are dispersed in deionized water under ultrasonic assistance for 30min, zinc borate is added, the temperature is increased to 80℃, reaction is carried out for 2h, and the nano composite flame-retardant filler is obtained after drying and grinding;
[0021] S3. The composite base obtained in S1, the filler obtained in S2, a bio-based thickening agent, a light-responsive hydrophobic adjuvant and a low-foaming wet dispersant are mixed and dispersed in a disperser at 1200rpm for 40min;
[0022] S4. The pH is adjusted to 9.0, and the product is filtered and packaged.
[0023] Further, the detailed steps of S1 are as follows:
[0024] S11. Butyl methacrylate, phosphoglycol methacrylate and deionized water are mixed in a mass ratio of 9:1, 0.1% ammonium persulfate is added as an initiator, reaction is carried out at 75-80℃ for 4h under nitrogen protection, and a phosphonate functionalized polyacrylate emulsion is obtained;
[0025] S12. The initiator is added dropwise in three times during the reaction, with an interval of 1 hour each time, and the reaction is assisted by ultrasound with a frequency of 40 kHz throughout the process;
[0026] S13. The potassium sodium silicate solution is preheated to 45 DEG C, and the modified emulsion obtained in S11 is slowly added, with the mass ratio of the two controlled to be 1:1, and ammonia water is used to adjust the pH to 8.8-9.0;
[0027] S14. Under stirring at 500 rpm, the silane coupling agent KH-570 with a mass fraction of 0.5% is added dropwise to the mixed solution at a dropwise adding speed of 2 mL / min, and after the dropwise adding is completed, the temperature is increased to 60 DEG C to continue the reaction for 2 hours, so as to form the inorganic phase The network and the organic phase polyacrylate chain form an interpenetrating structure.
[0028] Further, the specific steps of S2 are as follows:
[0029] S21. The nano is mixed with a citric acid solution with a mass fraction of 5% at a mass ratio of 1:10, and is treated at 60 DEG C under ultrasonic power of 200 W for 30 min, and after centrifugal separation, the citric acid modified with a negative charge on the surface is obtained;
[0030] S22. The Mg-Al layered double hydroxyl composite metal oxide LDH is added into the modified obtained in S21 at a mass ratio of 3:1, and is dispersed in deionized water under the assistance of ultrasonic waves with a frequency of 40 kHz for 30 min, and the pH of the system is controlled to be 9.0, so that the positive charge of the LDH layer and the negative charge are self-assembled through electrostatic adsorption, to form a composite with the LDH as the core and the as the shell;
[0031] S23. Zinc borate is added into the obtained mixed solution, and the mass of the zinc borate is 5% of the total mass of the LDH- composite, and the temperature is increased to 80 DEG C to react for 2 h, so that the zinc borate is bonded through a hydroxyl condensation reaction in the interlayer and on the surface of the LDH, to generate a stable loading structure;
[0032] S24. The reaction solution is spray dried to obtain primary particles with a particle size of , and then is ball milled under an inert atmosphere for 2 h to obtain a nano-composite flame-retardant filler with a specific surface area of 180-200 .
[0033] The application provides a construction method of building exterior wall paint, which comprises the following steps:
[0034] Q1. Substrate pretreatment; high-pressure water jet with pressure ≥ 20 MPa to remove loose layer and floating dust on the surface, then spray silane coupling agent KH-570 solution with pH = 9.0, stand for 30 min to form a chemical anchor layer;
[0035] Q2. Layered spraying and light activation; dilute the paint to a viscosity of 30-35 s, use airless spraying equipment to spray the first layer at a speed of 0.5 m / s, the wet film thickness is 80-100 μm, immediately after spraying, irradiate with a UV lamp with wavelength 365 nm and irradiance 1.0 W / cm² for 5 min to activate the super-hydrophobic properties of the light-responsive hydrophobic additive; after the bottom layer is tack-free, spray the second layer of original paint, the wet film thickness is 120 μm, the spraying direction is 90° intersected with the bottom layer, stand for 10 min after spraying, and irradiate with UV light for 10 min again;
[0036] Q3. Gradient curing; phase one: 40-50°C oven curing for 24 h, humidity ≤ 40%, to promote the interlayer hydroxyl condensation of LDH- flame-retardant filler; phase two: curing for 7 d under the condition of temperature 15-35°C and humidity 50-80%, during which deionized water is sprayed daily to promote the carbonization reaction of potassium sodium silicate binder and to form a dense network;
[0037] Q4. Post-processing; after curing, spray the surface with fluorosilicone curing agent to form a self-repairing hydrophobic film.
[0038] LDH (Mg-Al layered double hydroxyl composite metal oxide);
[0039] Chemical formula: ; a layered structure formed by the hydroxide layers of magnesium and aluminum bridged by common edge hydroxyl groups, which can adsorb exchangeable anions and water molecules between the layers, and has functions such as flame retardation and adsorption.
[0040] Nano cerium dioxide;
[0041] Cerium oxide nanoparticles with ultraviolet shielding and catalytic properties. After modification by citric acid, the surface is negatively charged, which is used to enhance the flame retardation and photocatalytic activity.
[0042] Zinc borate;
[0043] Chemical formula: ; a flame retardant that decomposes endothermically and releases flame-retardant gas when heated, loaded in the interlayer of LDH.
[0044] KH-570 (silane coupling agent);
[0045] Chemical name: γ-methacryloxypropyltrimethoxysilane; used for interfacial bonding of inorganic-organic phases, enhancing material compatibility.
[0046] Perfluorooctyltriethoxysilane;
[0047] Chemical formula: ; fluorosilane compound, used for modifying nanoparticles, imparting superhydrophobicity and light-responsive properties.
[0048] D4 (octamethylcyclotetrasiloxane);
[0049] Chemical formula: ; monomer of polydimethylsiloxane, used for preparing low-foam wetting dispersant.
[0050] Electrostatic self-assembly;
[0051] Spontaneously form core-shell structure through electrostatic attraction between oppositely charged particles.
[0052] Interpenetrating network structure;
[0053] Inorganic siloxane network and organic polyacrylate chains interpenetrate, enhancing the mechanical strength and weather resistance of the coating.
[0054] Light-responsive hydrophobicity;
[0055] Fluorosilicone-modified Under ultraviolet irradiation, the surface chemical structure changes, forming a superhydrophobic state.
[0056] Dynamic surface tension;
[0057] Wetting dispersant reduces the surface tension of the coating, reduces foaming, and improves filler dispersibility.
[0058] Specific surface area;
[0059] High specific surface area enhances the interfacial action of fillers and binders, improving flame retardation and catalytic efficiency.
[0060] Particle size ;
[0061] Nanocomposite flame retardant filler ; indicates that 50% of the particles have a particle size less than this value, affecting the leveling and film-forming properties of the coating.
[0062] PDMS (polydimethylsiloxane);
[0063] Structure: ; basic polymer of low-foam wetting dispersant, surface tension is reduced through polyether modification.
[0064] APS (ammonium persulfate);
[0065] Chemical formula: ; free radical initiator, used for polymerization of polyacrylate emulsion.
[0066] OI (oxygen index);
[0067] The minimum oxygen concentration required for the material to maintain combustion in oxygen-nitrogen mixed gas, such as OI≥30% is A2 grade flame retardant.
[0068] Contact angle;
[0069] Characterize surface hydrophobicity, the larger the angle, the stronger the hydrophobicity.
[0070] Smoke density (SDR);
[0071] Definition: The concentration of smoke generated when the material burns, the lower the value, the smaller the smoke hazard.
[0072] Heat release rate peak;
[0073] Unit: ; The maximum heat released per unit area when the material burns, the lower the value, the better the flame retardancy.
[0074] The beneficial effects achieved by the present application are:
[0075] First, the present application builds an interpenetrating structure of inorganic silicon-oxygen network and organic polymer chain by compounding potassium sodium silicate solution with phosphate functionalized polyacrylate emulsion. The inorganic phase gives the coating high hardness and weather resistance, while the organic phase provides flexibility and adhesion, and the synergistic effect of the two breaks through the performance limitations of traditional single base. This hybrid design significantly improves the mechanical strength and environmental adaptability of the coating, and enhances the bonding ability with the substrate, solving the problem of easy cracking and poor water resistance of traditional coatings.
[0076] Second, the present application adopts a core-shell structure of layered double hydroxyl composite metal oxide (LDH) and nano cerium oxide (cerium dioxide), and loads zinc borate flame retardant. The barrier effect of LDH layer and the UV shielding property of cerium dioxide form a complement, and the heat decomposition endothermic of zinc borate further strengthens the flame retardant level. This multi-level structure not only realizes high-efficiency flame retardation, but also delays material aging through photocatalysis and free radical capture mechanism, significantly improving the fire safety and long-term durability of the coating.
[0077] Third, the present application compiles hydroxypropyl guar gum and sodium alginate to form a three-dimensional network structure by hydrogen bonding and ionic bonding, creating a new application mode of natural polymer materials in paint thickening. This system has excellent rheological control ability and environmental friendly characteristics, ensuring the storage stability of the paint while avoiding the ecological burden of traditional synthetic thickening agents, embodying the innovative concept of sustainable resource utilization.
[0078] Fourthly, the present application realizes the intelligent combination of hydrophobicity and photocatalytic activity by fluorine-containing siloxane modified titanium dioxide nanoparticles. Ultraviolet irradiation triggers surface chemical reconstruction to form a dynamic superhydrophobic interface, endowing the coating with self-cleaning and antifouling ability. At the same time, the photocatalytic property can decompose pollutants, breaking through the limitation of single function of traditional hydrophobic materials, and providing an innovative solution for long-term cleaning of building coatings.
[0079] Fifthly, the present application designs a polyether-siloxane block structure dispersant, which realizes efficient dispersion of fillers and cell inhibition through steric hindrance effect and dynamic surface tension regulation. The industry problem of easy foaming and uneven dispersion of high solid content coatings is solved, ensuring film uniformity and surface flatness, simplifying the construction process, and significantly improving coating efficiency and quality stability.
[0080] Sixthly, the present application adopts a multi-stage composite and interface synergistic method in the preparation method, chemically bonds and interpenetrates the inorganic siloxane network and organic polymer chain by bridging with silane coupling agent, realizes the chemical bonding and interpenetrating structure of inorganic-organic phase; constructs LDH-cerium dioxide core-shell filler by using electrostatic self-assembly technology, forms a multi-level flame retardant system by combining in-situ loading of zinc borate; at the same time, the rheological properties of the system are regulated by the hydrogen bond-ion bond synergistic network of bio-based thickening agent. This method breaks through the limitation of simple mixing of traditional coating components, significantly enhances the material compatibility, filler dispersion uniformity and system stability, and endows the coating with excellent mechanical properties and flame retardant efficiency, while reducing production energy consumption and process complexity.
[0081] Seven, in terms of construction method, the present application realizes on-demand activation of superhydrophobic properties of the coating based on dynamic function activation and gradient structure regulation scheme by layering spraying combined with in-situ triggering of hydrophobic interface reconstruction by ultraviolet light; cross-spraying and staged curing strategy promotes carbonization of inorganic network and ordered arrangement of organic phase flexible chain, forming a dense gradient composite structure. This method effectively solves the problems of single function and weak interface bonding force in traditional coating, greatly improves the environmental adaptability, self-cleaning ability and long-term durability of the coating, while reducing construction energy consumption and maintenance cost, meeting the high-performance building protection requirements under complex climate conditions. BRIEF DESCRIPTION OF DRAWINGS
[0082] Figure 1 is the building exterior wall coating preparation method flow chart of the present application. DETAILED DESCRIPTION
[0083] The technical solutions in the present application will be described clearly and completely below in combination with the drawings in the present application. In addition, the forms of each structure described in the following embodiments are only examples, and the present application is not limited to each structure described in the following embodiments. All other embodiments obtained by those of ordinary skill in the art without creative labor fall within the scope of protection of the present application.
[0084] The building exterior wall coating of the present application is composed of the following core components;
[0085] The composite inorganic-organic hybrid film-forming binder is compounded by a sodium potassium silicate solution and a phosphate-modified polyacrylate emulsion at a mass ratio of 1:1.2. The sodium potassium silicate provides inorganic silicon-oxygen The network skeleton enhances weather resistance and hardness; the phosphate-modified polyacrylate emulsion is bonded to the inorganic phase through phosphate groups to form an organic-inorganic interpenetrating network, thereby improving adhesion and flexibility.
[0086] The nano-composite flame-retardant filler is compounded by Mg-Al layered double hydroxide LDH and citric acid-modified nano cerium oxide at a ratio of 3:1. The LDH interlayer is loaded with 5% zinc borate, which decomposes endothermically and releases flame-retardant gas upon heating; The ultraviolet shielding reduces the generation of free radicals, and cooperates with the 'layer barrier effect' of LDH to block the spread of fire. Both of them form a core-shell structure through electrostatic self-assembly, with a specific surface area of 180-200 , which enhances the dispersion of fillers and the efficiency of flame retardation.
[0087] The auxiliary functional components; the bio-based thickening agent hydroxypropyl guar gum / sodium alginate is compounded to stabilize the system through a hydrogen bond-ion bond network;
[0088] The light-responsive hydrophobic auxiliary agent fluorosilicone is modified to form a super-hydrophobic surface with a contact angle >150° under ultraviolet irradiation;
[0089] The low-foam wetting dispersant polyether-modified polysiloxane reduces the dynamic surface tension to below 30 mN / m, reduces foaming, and improves the dispersion of fillers.
[0090] The preparation method of the composite binder is as follows: the sodium potassium silicate solution is preheated to 45°C, the phosphate-modified polyacrylate emulsion is slowly added, and the silane coupling agent KH-570 is added dropwise, and the interpenetrating structure of inorganic silicon-oxygen network and organic chain is formed after 2 hours of reaction at 60°C.
[0091] The preparation method of the flame-retardant filler is as follows: Mg-Al LDH is synthesized by coprecipitation, and after hydrothermal crystallization and ion exchange, it is compounded with at pH=9.0 under ultrasonic self-assembly, forming a core-shell structure with LDH as the core and The complex is then loaded with zinc borate and high specific surface area nano filler 5-8 is obtained by a spray drying-milling process Particle size.
[0092] Nanometer The modified titanium tetrabutoxide is hydrolyzed to form nanometer Then, the fluorine-containing segment is grafted by siloxane condensation by refluxing with perfluorooctyltriethoxysilane at 80°C for 6 hours, and the super-hydrophobic property is activated by ultraviolet irradiation for 2 hours.
[0093] Biobased thickening agent; guar gum is modified by hydroxypropylation and compounded with sodium alginate at a ratio of 2:1 to form a synergistic thickening network at 50°C.
[0094] Low-foaming dispersant; polydimethylsiloxane (PDMS) is introduced into a polyether segment by hydrosilylation with an allyl polyoxyethylene ether to form a block structure to reduce foaming.
[0095] Coating mixing and application method; the composite binder, nano filler, thickening agent, hydrophobic aid and dispersant are mixed and dispersed at 1200 rpm for 40 minutes, and then filtered after adjusting the pH to 9.0.
[0096] During construction, layer spraying is used; the first wet film is sprayed and the hydrophobicity is activated immediately by 365 nm ultraviolet light, the second cross-spraying is sprayed and secondary curing is performed. Finally, a dense network is formed by gradient curing at 40-50°C drying + room temperature carbonization, and a fluorine-containing siloxane curing agent is sprayed on the surface to realize self-repairing hydrophobic film.
[0097] The building exterior wall coating of the present application is preferably made from the following raw materials by weight:
[0098] Composite inorganic-organic hybrid film-forming binder: 50 parts, compounded from a sodium potassium silicate solution and a modified polyacrylate emulsion of 3% mass fraction of phosphate ester functional monomer at a mass ratio of 1:1.2;
[0099] Nano-composite flame-retardant filler: 28 parts, including a composite of Mg-Al layered double hydroxyl composite metal oxide (LDH) and nano cerium oxide at a mass ratio of 3:1 , wherein the LDH is loaded with 5% mass fraction of zinc borate;
[0100] Biobased thickening agent: 2 parts, compounded from hydroxypropyl guar gum and sodium alginate at a mass ratio of 2:1;
[0101] Light-responsive hydrophobic aid: 0.8 parts, titanium dioxide nanoparticles modified with fluorine-containing siloxane;
[0102] Low-foaming wetting dispersant: 0.7 parts, polyether-modified polysiloxane;
[0103] Deionized water: balance.
[0104] Preparation of Mg-Al layered bishydroxy composite metal oxide; the chemical formula of the Mg-Al layered bishydroxy composite metal oxide is , its preparation process is as follows:
[0105] Will and Prepare mixed salt solution in a molar ratio of 3:1, and mix with The precipitant was co-precipitated for 2 hours and the precursor was obtained by centrifugation and washing. ;
[0106] Subsequently, a high-crystalline intermediate was obtained by hydrothermal treatment at 120-140 °C for 12 h and spray drying;
[0107] Finally, disperse it in The solution was ion exchanged at 50℃ for 24 hours. Completely replace interlayer After washing and drying, the target product was obtained .
[0108] Surface modification and composite of nano-cerium oxide; the nano-cerium oxide After surface modification with citric acid, it forms a core-shell structure with LDH through electrostatic self-assembly. Uniformly coated on the surface of LDH, with a specific surface area of 180-200 The main body of LDH is made of and Brucite-like structures formed by edge-sharing hydroxyl bridging layered structure, Partly Isomorphous substitution, the layers carry positive charges; exchangeable anions and water molecules are adsorbed between the layers through electrostatic interaction to form an intercalated structure with an interlayer spacing of 0.77nm.
[0109] Preparation of bio-based thickener: natural guar gum is used as raw material, reacted with propylene oxide in a molar ratio of 1:1.2 at 60°C under alkaline conditions for 4 hours, hydroxyl groups are introduced through hydroxypropyl substitution reaction, and hydroxypropyl guar gum is obtained after ethanol precipitation and drying; brown algae is used as raw material, decalcified with dilute hydrochloric acid, extracted with sodium carbonate, filtered and ethanol precipitated to obtain high-purity sodium alginate; hydroxypropyl guar gum and sodium alginate are dissolved in deionized water in a mass ratio of 2:1, stirred at 50°C for 1 hour to form a hydrogen bond-ionic bond synergistic network, and finally a bio-based thickener is obtained.
[0110] Preparation of photo-responsive hydrophobicity assistant; tetrabutyl titanate was mixed with anhydrous ethanol, hydrolyzed by dropwise adding dilute nitric acid, aged at 60℃ for 12h, and centrifuged to obtain titanium dioxide with particle size of 20-50nm ; fluorine-containing chain segment was dispersed in isopropyl alcohol, and perfluorooctyl triethoxysilane was added, and the mixture was refluxed at 80℃ for 6h to graft the fluorine-containing chain segment on the surface through siloxane hydrolysis and condensation ; the photo-responsive property was strengthened by ultraviolet irradiation for 2h, and the specific surface area of the final product was ≥150 .
[0111] Preparation of low-foaming wetting dispersant; octamethylcyclotetrasiloxane D4 was used as monomer, hexamethyldisiloxane was used as end-capping agent, and the mixture was subjected to ring-opening polymerization at 90℃ for 6h under the catalysis of 1% mass fraction of sulfuric acid to obtain polydimethylsiloxane PDMS with viscosity of 500-800mPa·s; PDMS was reacted with allyl polyoxyethylene ether at a molar ratio of 1:1.2 under the action of platinum catalyst through silane hydride addition reaction at 110℃ for 5h to introduce polyether chain segment and form polyether-siloxane block structure; the dynamic surface tension was reduced to ≤30mN / m through the steric hindrance effect of the polyether chain segment, and the final product had foaming height of <10mm.
[0112] Preparation method of building exterior wall coating; preparation of composite binder S1; synthesis of phosphate-functionalized polyacrylate emulsion
[0113] Monomer: butyl methacrylate BA + phosphoglycol methacrylate PEG-PMA
[0114] Initiator: ammonium persulfate APS
[0115] Reaction formula: ;
[0116] The phosphate group provides bonding sites with inorganic phases.
[0117] Potassium sodium silicate reacts with silane coupling agent KH-570:
[0118] Reaction formula: ;
[0119] Interpenetrating network is formed with the polyacrylate chain to enhance mechanical strength.
[0120] Preparation of nanocomposite flame-retardant filler S2; preparation of Mg-Al LDH precursor
[0121] Co-precipitation reaction ;
[0122] Ion exchange and a stable layered structure is formed.
[0123] Surface modification and complexation:
[0124] Citric acid With Surface hydroxyl groups coordinate negative charge:
[0125]
[0126] LDH positive charge and Form core-shell structure by electrostatic self-assembly.
[0127] Hydroxyl condensation reaction:
[0128]
[0129] Synthesis of bio-based thickener; ring-opening reaction of guar with propylene oxide:
[0130]
[0131] Introduce hydroxypropyl groups to improve water solubility and thickening efficiency.
[0132] Sodium alginate extraction:
[0133] Brown algae is acid Decalcification, alkali Extraction, precipitation of sodium alginate .
[0134] Preparation of light-responsive hydrophobic adjuvant; tetrabutyl titanate Hydrolysis:
[0135]
[0136] Hydrolysis and condensation of perfluorooctyltriethoxysilane PFOTES:
[0137]
[0138] Synthesis of low-foaming wetting dispersant; octamethylcyclotetrasiloxane D4 polymerization:
[0139]
[0140] Silicon-hydrogen addition reaction PDMS and allyl polyoxyethylene ether:
[0141]
[0142] Inorganic Network blocks water penetration, enhances weather resistance. Phosphate groups enhance interfacial bonding, improve adhesion. LDH and zinc borate endothermic decomposition release And , forming a glassy barrier layer. The fluorosilicon segment reduces surface energy, imparting superhydrophobicity. Photocatalytic decomposition of pollutants, improving self-cleaning performance. Biological thickening agent hydrogen bond network inhibits filler sedimentation, stabilizing the system.
[0143] Example 1, the building exterior wall coating in this example uses the following ingredients:
[0144] Table 1 Building exterior wall coating ingredients used in Example 1
[0145] Ingredient name Parts by weight Specific parameters and composition Composite inorganic-organic hybrid film-forming binder 50 Potassium sodium silicate solution and 3% phosphate ester modified polyacrylate emulsion were compounded at a mass ratio of 1:1.2, 22.7 parts of potassium sodium silicate solution, and 27.3 parts of modified emulsion Nano-composite flame-retardant filler 28 Mg-Al LDH 21 parts and citric acid modified nanometer cerium dioxide 7 parts were compounded at a ratio of 3:1, with LDH loaded with 5% zinc borate 1.05 parts Bio-based thickening agent 2 Hydroxypropyl guar gum 1.33 parts and sodium alginate 0.67 parts were compounded at a ratio of 2:1 Light-responsive hydrophobicity aid 0.8 Fluorosiloxane modified titanium dioxide nanoparticles with a particle size of 35 nm and a specific surface area of 160 m² / g Low-foam wetting dispersant 0.7 Polyether modified polysiloxane with a viscosity of 650 mPa·s and a foaming height of 8 mm Deionized water Balance pH = 9.0, total amount made up to 100%
[0146] The following preparation process is used:
[0147] 9 kg of butyl methacrylate and 1 kg of methacrylate phosphate ethylene glycol ester are reacted at 80°C under nitrogen protection for 4 hours, 10 g of ammonium persulfate initiator is added in 3 times, and 40 kHz ultrasonic wave is used throughout the process. A phosphonate modified polyacrylate emulsion is prepared. Then 22.7 kg of potassium sodium silicate solution is preheated to 45°C and mixed with 27.3 kg of modified emulsion at a mass ratio of 1:1.2, the pH is adjusted to 9.0, 1.25 kg of silane coupling agent KH-570 is added dropwise, and the mixture is reacted at 60°C for 2 hours to form an inorganic-organic interpenetrating network. 7 kg of nano cerium dioxide is treated with 70 kg of 5% citric acid solution at 60°C and 200W ultrasonic wave for 30 minutes, and then centrifuged and mixed with 21 kg of Mg-Al LDH with pH=9.0 to form a core-shell structure by 40 kHz ultrasonic self-assembly. Add 1.05 kg of zinc borate to a total mass of 5%, react at 80°C for 2 hours, spray dry to obtain D50=6μm particles, and ball mill to a specific surface area of 190m² / g.
[0148] Mix 50 kg of composite base, 28 kg of nano filler, 2 kg of biological thickening agent hydroxypropyl guar gum 1.33 kg + sodium alginate 0.67 kg, 0.8 kg of fluorosilicon modified titanium dioxide with particle size of 35 nm, and 0.7 kg of polyether modified polysiloxane dispersant, disperse at high speed for 40 minutes at 1200 rpm, adjust the pH to 9.0, add 0.3 kg of ammonia water, filter through a 200 mesh screen, and the final coating viscosity is stable at 32 s, with no sedimentation during long-term storage, and the viscosity change is only 2%.
[0149] Comparative Example 1: In this comparative example, a commercially available silicone-acrylate emulsion exterior wall coating is used, which mainly contains pure acrylic emulsion, titanium dioxide, and heavy calcium, containing APEO wetting agent;
[0150] Experimental method:
[0151] Water resistance test: Prepare 150mm x 70mm cement mortar test panel, coated with paint and dried for 7 days. Immersed in 23±2℃ deionized water for 168 hours, after taking out and wiping dry, observe whether the coating is blistering, peeling off. According to the standard rating: 0 level no change to 5 level serious damage.
[0152] Adhesion test: Draw 1mm x 1mm 100 squares on the surface of the coating with a grid marker, and the scratch depth reaches the substrate. Paste the grid area with transparent tape and quickly tear it off, calculate the shedding rate, the percentage of the total area. Rating standard: 0 level 0% shedding to 5 level >65% shedding.
[0153] Flame retardancy oxygen index test: Prepare 100mm x 10mm x 3mm samples, place them in an oxygen index instrument, adjust the oxygen / nitrogen ratio, and measure the minimum oxygen concentration OI value required for the material to continue burning for 30 seconds or 50mm length. Classification: A2 level OI≥30%, B1 level 24%≤OI<30%.
[0154] UV aging test, using UVA-340 lamp tube to simulate sunlight ultraviolet, irradiance 0.76W / m², blackboard temperature 63±3℃, relative humidity 50±5%. After 2000 hours, use color difference meter to measure the color difference of the coating ΔE ΔE≤1 is no change, ΔE≥3 is obvious discoloration.
[0155] Self-cleaning test: evenly spray graphite powder and vegetable oil 1:1 simulated pollutants on the surface of the coating, stand for 24 hours. Rinse with 0.2MPa water pressure for 30 seconds, calculate the pollutant removal rate clean area / polluted area x 100%.
[0156] Storage stability test: seal the paint in a 500mL container, stand at room temperature 23±2℃ for 6 months. Observe whether it is layered, caked, and measure the viscosity change rate using a rotational viscometer. The percentage difference between the initial viscosity and the final viscosity.
[0157] Contact angle test method: use contact angle measuring instrument sessile drop method to measure static contact angle. The sample is evenly coated on the glass substrate, the test liquid drop volume is 2μL, and the average value of three measurements is taken.
[0158] Self-cleaning efficiency test method: mix graphite powder and soybean oil at a ratio of 1:1 to make a simulated pollutant. Use an airbrush to evenly apply the pollutant at a coating amount of 2.0±0.2g / m², and cure at room temperature for 24h. Use a spray device with water pressure 0.2MPa, nozzle diameter 1mm, vertical distance 30cm, and rinse for 30s. Analyze the area ratio of the clean area.
[0159] Table 2 Experimental data and results of Example 1 and Comparative Example 1
[0160]
[0161] As can be seen from Table 2, the composite base potassium sodium silicate + phosphate ester modified emulsion forms an interpenetrating network structure, the inorganic phase fills the organic phase pores, and blocks water penetration. The pure organic emulsion of Comparative Example 1 has poor water resistance due to the presence of many hydrophilic groups; the inorganic-organic hybrid structure of Example 1 significantly reduces the water absorption.
[0162] In the LDH-cerium dioxide composite filler, the interlayer zinc borate of LDH decomposes endothermically, and the ultraviolet shielding effect of cerium dioxide reduces the generation of free radicals. The OI value of Example 1 is 38%, which is much higher than that of Comparative Example 1 (24%), and the ultraviolet aging ΔE is only 1.2, while that of Comparative Example 1 is 13.8.
[0163] The light-responsive hydrophobic aid fluorine-silicon modified titanium dioxide has super-hydrophilic-super-hydrophobic switching characteristics under ultraviolet excitation, and pollutants are easily washed away by rainwater. The contact angle of Example 1 is 152°, and the self-cleaning efficiency is 95%; the efficiency of Comparative Example 1 without hydrophobic aid is only 40%.
[0164] The bio-based thickening agent guar gum + sodium alginate stabilizes the filler dispersion through hydrogen bonding and electrostatic interaction, and inhibits sedimentation. The viscosity change of Example 1 is only 2%, while the traditional thickening agent HEC of Comparative Example 1 is easily separated, and is stratified after 3 months of storage.
[0165] The coating of the present application is significantly superior to commercially available products in water resistance, flame retardancy, self-cleaning property and storage stability, verifying the synergistic effect of composite base, nano filler and bio thickening agent.
[0166] Example 2: Based on the formulation of Example 1, the mass ratio of composite base: potassium sodium silicate solution to modified polyacrylate emulsion is 1:1.2, and the construction process is as follows:
[0167] Substrate pretreatment: use 20MPa high pressure water jet to remove cement-based surface dust, spray silane coupling agent KH-570 solution with pH=9.0, and stand for 30 minutes to form a chemical anchor layer. Layered spraying and photoactivation: dilute the coating to a viscosity of 32s-cup, the first spraying wet film thickness is 90μm, immediately after spraying, irradiate with a 365nm ultraviolet lamp with an irradiance of 1.0W / cm² for 5 minutes; the second wet film thickness is 120μm, after cross-spraying at a 90° direction, stand for 10 minutes, and irradiate again with a 365nm ultraviolet lamp for 10 minutes. Gradient curing: the first stage is 45℃ oven curing for 24 hours with humidity ≤40%, the second stage is 25℃, humidity 60% curing for 7 days, and spray deionized water every day. Post-treatment: spray fluorine-containing siloxane curing agent to form a self-repairing hydrophobic film.
[0168] Comparative Example 2: only use 50 parts of potassium sodium silicate solution, the preparation method is the same as that of Example 1, but no polyacrylate emulsion is added, and the ultraviolet activation step is omitted in the construction process.
[0169] Comparative Example 3: Using only phosphonate modified polyacrylate emulsion 50 parts, without adding potassium sodium silicate solution, curing conditions and construction consistent with Example 2.
[0170] Experimental methods and test indicators:
[0171] Impact resistance: 1 kg drop hammer from 50 cm free fall impact on the surface of the coating, observe whether cracking. Rating criteria: 0 level no cracks to 4 level serious cracking.
[0172] Pencil hardness: with Mitsubishi pencil hardness range 6B-9H at 45° angle on the surface of the coating scratch, the highest hardness level without scratch as the coating hardness.
[0173] Table 3 Experimental data and results of Example 2 and Comparative Example 2, Comparative Example 3
[0174] Index Example 2 Comparative Example 2 Comparative Example 3 Water resistance 168h foaming rate 0% 100%, severe foaming 40%, partial foaming Adhesion loss rate 0%, level 1 18%, level 3 8%, level 2 Pencil hardness 4H 2H 3H Impact resistance 50 cm No cracks Cracking level 4 Mild cracking level 2
[0175] Example 2 by inorganic-organic hybrid base sodium silicate Si-O-Si network and flexible chain of polyacrylate interpenetration and stratified UV curing process, significantly improve the water resistance without blister and adhesion 0% off, while the hardness 4H and impact resistance is better than single component system. Comparative Example 2 due to the high brittleness of pure inorganic phase, resulting in poor adhesion and 18% off and impact cracking, Comparative Example 3 due to the insufficient water resistance of the organic phase, blistering 40%. Show that the synergistic effect of composite base and gradient construction process, the comprehensive performance is better than traditional single component coating.
[0176] Example 3: based on the formulation and preparation process of Example 1, nano filler is LDH-cerium dioxide composite, mass ratio 3:1, loaded with 5% zinc borate, S2 step preparation: after ultrasonic self-assembly of LDH and citric acid modified cerium dioxide, load zinc borate, spray drying and ball milling to specific surface area 190 m² / g. Construction method consistent with Example 2.
[0177] Comparative Example 4: using only LDH 28 parts, without adding cerium dioxide and zinc borate.
[0178] Comparative Example 5: using only cerium dioxide 28 parts, without loading zinc borate.
[0179] Experimental methods and test indicators:
[0180] Smoke density SDR: using smoke density tester, burning sample under 50 kW / m² radiant heat flux, measuring the maximum smoke density value SDR.
[0181] Peak heat release rate: using cone calorimeter, testing under 50 kW / m² radiant power, recording the peak heat release rate per unit area kW / m².
[0182] Smoke density SDR test method: using smoke density tester, sample size 75x75x3mm, radiant heat flux 50kW / m2, record the maximum smoke density within 600s.
[0183] Heat release rate peak test method: sample size 100x100x3mm, horizontally placed under the radiant cone, radiant power 50kW / m2, record the peak heat release rate per unit area within 180s.
[0184] Table 4 Experimental data and results of Example 3 and Comparative Examples 4, 5
[0185] Index Example 3 Comparative Example 4 Comparative Example 5 Oxygen index OI 38% A level 2 28% B level 1 22% B level 1 Smoke density SDR 45 78 92 Ultraviolet aging ΔE 2000h 1.2 3.5 4.8 Peak heat release rate 85 kW / m² 145 kW / m² 180 kW / m²
[0186] The LDH-cerium dioxide core-shell structure cerium dioxide coated LDH of Example 3 improves the OI value to A2 level 38% through the triple mechanism of "layer barrier + ultraviolet shielding + zinc borate heat absorption", reduces the smoke density by 58% SDR=45, and the ultraviolet aging color difference ΔE is only 1.2. Comparative Example 4 lacks the ultraviolet shielding effect of cerium dioxide ΔE=3.5, and Comparative Example 5 has no LDH barrier effect with a heat release peak of 180kW / m2, and the flame retardation and aging resistance performance are significantly reduced. The multi-level structure design of the nano-composite filler significantly improves the flame retardation and durability of the coating.
[0187] Example 4: Based on the formulation and preparation method of Example 1, 0.8 parts of fluorine-silicon modified titanium dioxide is added, and after hydrolysis of tetrabutyl titanate, it is grafted with perfluorooctyltriethoxysilane, and ultraviolet irradiation is performed for 2 hours. The construction method is consistent with Example 2.
[0188] Comparative Example 6: No fluorine-silicon modified titanium dioxide is added, and the other ingredients are the same as Example 1.
[0189] Experimental methods and test indicators:
[0190] Contact angle test method: use contact angle measuring instrument to measure static contact angle by drop method. The sample is evenly coated on the glass substrate, the test liquid drop volume is 2μL, and the average value of three measurements is taken.
[0191] Experimental method of surface energy: use contact angle instrument to measure the contact angles of water polar liquid and diiodomethane nonpolar liquid, and calculate the surface energy mN / m by Owens-Wendt formula.
[0192] Photocatalytic degradation rate test method: prepare 10mg / L methylene blue solution, immerse the sample size 50x50mm in the solution, use 365nm ultraviolet light source intensity 1.0mW / cm2 vertical irradiation for 4h, and use UV-Vis spectrophotometer to measure the absorbance change at 664nm.
[0193] Surface energy calculation method supplement: using Owens-Wendt two-liquid method, using contact angle instrument to measure the contact angle of deionized water polar liquid and diiodomethane nonpolar liquid respectively, calculating the dispersion component and the polarity component, and the total is the total surface energy.
[0194] Table 5 Experimental data and results of example 4 and comparative example 6
[0195] Index Example 4 Comparative Example 6 Contact angle 152° 85° Self-cleaning efficiency 95% 40% Photocatalytic degradation rate 4h 88% 5% Surface energy 12 mN / m 45 mN / m
[0196] The fluorosilicon modified titanium dioxide of example 4 forms a super-hydrophobic surface with a contact angle of 152° by ultraviolet activation, the surface energy is as low as 12 mN / m, pollutants are easily washed away by rain, the self-cleaning efficiency is 95%, and the photocatalytic degradation rate reaches 88%. Comparative example 6 has a hydrophilic surface with a contact angle of 85°, which easily adsorbs pollutants, and the self-cleaning efficiency is only 40%. The light-responsive hydrophobic additive significantly improves the self-cleaning and stain resistance of the coating through the synergistic effect of “low surface energy + photocatalysis”.
[0197] Example 5: Based on the formulation and preparation method of example 1, the thickening agent is a 2:1 complex of hydroxypropyl guar gum and sodium alginate. The hydroxypropyl guar gum is subjected to a propylene oxide substitution reaction at 60°C, and the sodium alginate is dissolved in water after being extracted with brown algae alkali at 50°C and stirred for 1 hour. The construction method is the same as example 2.
[0198] Comparative example 7: only hydroxypropyl guar gum 2 parts is used.
[0199] Comparative example 8: only sodium alginate 2 parts is used.
[0200] Experimental method and test index:
[0201] Zeta potential test method: use Malvern Zetasizer Nano ZS90 instrument, take the dilution to 0.1% mass fraction of the coating suspension, measure three times at 25°C and take the average value.
[0202] Settlement phenomenon quantification method: fill the coating into a 250 mL graduated cylinder with a stopper, record the settlement layer height ratio after standing at room temperature for 6 months.
[0203] ; Wherein H0 is the initial height, Ht is the height of the supernatant after standing.
[0204] Table 6 Experimental data and results of example 5 and comparative examples 7 and 8
[0205] Index Example 5 Comparative Example 7 Comparative Example 8 Initial viscosity mPa·s 3200 2800 2500 6-month viscosity change rate +2% +15% +12% Zeta potential mV -45 -20 -35 Settling phenomenon No Layered supernatant 5% Flocculation clumping
[0206] The hydroxypropyl guar of Example 5 forms a three-dimensional network by hydrogen bonding and anionic electrostatic repulsion of sodium alginate, with a Zeta potential of -45 mV, a viscosity change of only 2% after 6 months of storage, and no sedimentation. Comparative Example 7 is delaminated due to a single hydrogen bonding network with a Zeta potential of -20 mV, and Comparative Example 8 is flocculated due to insufficient electrostatic repulsion with a Zeta potential of -35 mV. The synergistic effect of the compounding of the bio-based thickening agent significantly improves the storage stability of the coating, meeting the green and environmentally friendly requirements.
[0207] The above only describes the preferred embodiments of the present application and is not intended to limit the present application. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A building exterior wall coating, characterized in that: It is made from the following raw materials in parts by weight: Composite inorganic-organic hybrid film-forming base: 50 parts, prepared by mixing potassium sodium silicate solution and modified polyacrylate emulsion containing 3% phosphate functional monomer at a mass ratio of 1:1.2; Nanocomposite flame retardant filler: 28 parts, including a composite of Mg-Al layered dihydroxy composite metal oxide LDH and nano-cerium dioxide in a mass ratio of 3:1; Bio-based thickener: 2 parts, prepared by mixing hydroxypropyl guar gum and sodium alginate in a mass ratio of 2:1; Photoresponsive hydrophobic additive: 0.8 parts, which is fluorinated silicone-modified titanium dioxide nanoparticles; Low foam wetting and dispersing agent: 0.7 parts, polyether modified polysiloxane; Deionized water: balance.
2. The exterior wall coating according to claim 1, characterized in that: The chemical formula of the Mg-Al layered bishydroxy composite metal oxide is , its preparation process is as follows: First, and Prepare mixed salt solution in a molar ratio of 3:1, and mix with The precipitant was co-precipitated for 2 hours and the precursor was obtained by centrifugation and washing. ; Then hydrothermally treated at 120-140℃ for 12 hours, spray dried to obtain a high crystallinity intermediate; finally dispersed in The solution was ion exchanged at 50℃ for 24 hours. Completely replace interlayer After washing and drying, the target product was obtained .
3. The exterior wall paint according to claim 2, characterized in that: The preparation method of the bio-based thickener is as follows: natural guar gum is used as a raw material, reacted with propylene oxide in a molar ratio of 1:1.2 at 60°C under alkaline conditions for 4 hours, and a hydroxyl group is introduced through a hydroxypropyl substitution reaction. Hydroxypropyl guar gum is obtained after ethanol precipitation and drying; brown algae is used as a raw material, decalcified with dilute hydrochloric acid, extracted with sodium carbonate, filtered, and then ethanol precipitated to obtain high-purity sodium alginate; hydroxypropyl guar gum and sodium alginate are dissolved in deionized water in a mass ratio of 2:1, and stirred at 50°C for 1 hour to form a hydrogen bond-ionic bond synergistic network, and finally the bio-based thickener is obtained.
4. The exterior wall paint according to claim 3, characterized in that: The preparation method of the photoresponsive hydrophobic additive is as follows: tetrabutyl titanate is mixed with anhydrous ethanol, diluted nitric acid is added dropwise for hydrolysis, aged at 60°C for 12 hours, and centrifuged to obtain particles with a size of 20-50 nm. ;Will Dispersed in isopropanol, added perfluorooctyl triethoxysilane, refluxed at 80℃ for 6h, and condensed by hydrolysis of siloxane. Surface grafting of fluorinated segments; Enhanced photoresponse characteristics: UV irradiation for 2 hours, the final product has a specific surface area of ≥150 .
5. The exterior wall paint according to claim 4, characterized in that: The preparation method of low foam wetting and dispersing agent is as follows: Octamethylcyclotetrasiloxane D4 was used as a monomer and hexamethyldisiloxane as a capping agent. Ring-opening polymerization was carried out at 90°C for 6 h in the presence of 1% mass fraction sulfuric acid to obtain polydimethylsiloxane (PDMS) with a viscosity of 500-800 mPa·s. PDMS was reacted with allyl polyoxyethylene ether at a molar ratio of 1:1.2 via a hydrosilylation reaction at 110°C for 5 h in the presence of platinum catalyst to introduce polyether segments and form a polyether-siloxane block structure. The dynamic surface tension was reduced to ≤30 mN / m through the steric hindrance effect of the polyether segments, and the bubble height of the final product was <10 mm.
6. The method for preparing the exterior wall coating according to claim 5, wherein: The following steps are involved: S1. The potassium sodium silicate solution and the modified polyacrylate emulsion were premixed at 50°C and 300 rpm for 1 h to form a composite base; S2. Combine LDH with nanoparticles The nanocomposite flame retardant filler was obtained by dispersing the mixture in deionized water under ultrasound assistance for 30 minutes, adding zinc borate, heating the mixture to 80°C and reacting the mixture for 2 hours, and then drying and grinding the mixture. S3. The composite base obtained from S1, the filler obtained from S2, and a bio-based thickener, a light-responsive hydrophobic additive, and a low-foaming wetting dispersant were mixed and dispersed in a disperser at 1200 rpm for 40 min; S4. Adjust the pH to 9.0, filter and package.
7. The preparation method according to claim 6, characterized in that The detailed steps of S1 are as follows: S11. Butyl methacrylate and ethylene glycol methacrylate phosphate were mixed with deionized water in a mass ratio of 9:1, and 0.1% by mass of ammonium persulfate was added as an initiator. The mixture was reacted at 75-80°C under nitrogen for 4 h to obtain a phosphate-functionalized polyacrylate emulsion. S12. The initiator was added dropwise three times during the reaction, each time at an interval of 1 h, and the entire reaction was assisted by ultrasound at a frequency of 40 kHz; S13. Preheat the potassium sodium silicate solution to 45°C and slowly add the modified emulsion obtained in S11 to control the mass ratio of the two to be 1:
1. At the same time, adjust the pH to 8.8-9.0 with aqueous ammonia; S14. Under stirring at 500 rpm, add 0.5% mass fraction of silane coupling agent KH-570 dropwise to the mixture at a rate of 2 mL / min. After the addition is complete, heat to 60°C and continue the reaction for 2 h to form an inorganic phase. Interpenetrating structure of network and organic phase polyacrylate chains.
8. The preparation method according to claim 7, characterized in that The specific steps of S2 are as follows: S21. Nano It was mixed with 5% citric acid solution at a mass ratio of 1:10, treated at 60 ° C and ultrasonic power 200 W for 30 minutes, and centrifuged to obtain citric acid-modified films with negative charges on the surface. ; S22. Modification of Mg-Al layered dihydroxy composite metal oxide LDH with S21 Add deionized water at a mass ratio of 3:1, disperse for 30 minutes under the assistance of ultrasound at a frequency of 40kHz, and control the pH of the system to 9.0 so that the positive charge of the LDH layer is Negative charges self-assemble through electrostatic adsorption to form LDH as the core, It is a composite of shells; S23. Add zinc borate to the resulting mixture , whose mass is LDH- 5% of the total mass of the complex, heated to 80℃ for 2h, so that zinc borate was deposited between the LDH layers and The surface is bonded through hydroxyl condensation reaction to generate a stable loading structure; S24. The reaction solution is spray-dried to obtain a particle size The primary particles were then ball milled for 2 h under an inert atmosphere to obtain a specific surface area of 180-200 Nanocomposite flame retardant filler.
9. The construction method of the exterior wall coating according to claim 5, wherein: The steps include: Q1. Substrate pretreatment: Use a high-pressure water jet with a pressure of ≥20MPa to remove dust and loose layers on the substrate, then spray a silane coupling agent KH-570 solution with a pH of 9.0 and let it stand for 30 minutes to form a chemical anchoring layer; Q2. Layered spraying and light activation; dilute the paint to a viscosity of 30-35s, use airless spray equipment to spray the first coat at a speed of 0.5m / s, and the wet film thickness is 80-100 Immediately after spraying, irradiate with UV light of 365nm wavelength and 1.0W / cm² for 5 minutes to activate the super hydrophobic properties of the light-responsive hydrophobic additive; after the bottom layer is dry, spray the second coat of original paint with a wet film thickness of 120 , the spraying direction is 90° across the bottom layer, let it stand for 10 minutes after spraying, and then irradiate with UV light for 10 minutes again; Q3. Gradient curing; Stage 1: Curing in a drying room at 40-50℃ for 24 hours, humidity ≤ 40%, to promote LDH- The interlayer hydroxyl condensation of flame retardant filler; Stage 2: Curing for 7 days under the conditions of temperature 15-35℃ and humidity 50-80%, during which deionized water is sprayed every day to promote the combination of potassium sodium silicate base material and flame retardant filler; Stage 2: Curing for 7 days under the conditions of temperature 15-35℃ and humidity 50-80%, during which time deionized water is sprayed every day to promote the combination of potassium sodium silicate base material and flame retardant filler; Stage 2: Curing for 7 days under the conditions of temperature 15-35℃ and humidity 50-80% The carbonization reaction forms a dense network; Q4. Post-treatment: After curing is completed, spray the surface with a fluorinated silicone curing agent to form a self-repairing hydrophobic film.
Citation Information
Patent Citations
Efficient flame-retardant antibacterial self-cleaning bio-based composite coating and preparation method thereof
CN116770587A
Metal roof derusting self-cleaning waterproof coating and preparation method thereof
CN119552546A
Efficient flame-retardant waterproof and fireproof coating for special humid environment and preparation method of efficient flame-retardant waterproof and fireproof coating
CN120665494A
Compositions with Improved Dirt Pickup Resistance Comprising Layered Double Hydroxide Particles
US20110040006A1
Transparent flame-retardant thermal-insulating UV-blocking polymer composite film, preparation method and uses thereof
US20160243583A1
Cited By
Self-cleaning hydrophobic building membrane material with micro-nano coarse structure
CN121554948A